2015
DOI: 10.1007/s40806-015-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

“Drawing” Conclusions About Perceptions of Ideal Male and Female Body Shapes

Abstract: Preferences for bodily traits (e.g., waist-to-hip ratio; WHR) have been widely documented through the use of stimulus sets (e.g., line drawings, photographs). The purpose of the present study was to explore preferences for bodily traits using a method that does not constrain the range of possible values for each trait. Participants drew a figure depicting the most attractive member of the opposite sex they could imagine and a figure depicting a member of their own sex that they believed members of the opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Individuals with higher mate value are more desirable as mates than those with lower mate value. Mate value comprises physical traits (e.g., higher shoulder‐to‐hip ratio in men, lower waist‐to‐hip ratio in women, greater facial symmetry in both sexes; Cloud & Perilloux, ; Hughes & Gallup, ; Marlowe, Apicella, & Reed, ; see Rhodes, , for a review; Singh, ) and social attributes (e.g., social status, generosity, intelligence, resource‐earning potential, history of fidelity; Miller, ; Mogilski, Wade, & Welling, ; Shackelford, Schmitt, & Buss, ) that signal health, genetic quality, fertility, parenting skills, or likelihood and quality of investment in offspring (Buss & Shackelford, ; Gangestad & Simpson, ; Johnston & Franklin, ; Miller, ; Pérusse, ; Singh, ). Self‐report measures of mate value typically ask participants to self‐assess socially desirable and sexually desirable traits such as physical attractiveness, health, industriousness, intelligence, social status, relationship fidelity, generosity, and financial prospects.…”
Section: Mate Retentionmentioning
confidence: 99%
“…Individuals with higher mate value are more desirable as mates than those with lower mate value. Mate value comprises physical traits (e.g., higher shoulder‐to‐hip ratio in men, lower waist‐to‐hip ratio in women, greater facial symmetry in both sexes; Cloud & Perilloux, ; Hughes & Gallup, ; Marlowe, Apicella, & Reed, ; see Rhodes, , for a review; Singh, ) and social attributes (e.g., social status, generosity, intelligence, resource‐earning potential, history of fidelity; Miller, ; Mogilski, Wade, & Welling, ; Shackelford, Schmitt, & Buss, ) that signal health, genetic quality, fertility, parenting skills, or likelihood and quality of investment in offspring (Buss & Shackelford, ; Gangestad & Simpson, ; Johnston & Franklin, ; Miller, ; Pérusse, ; Singh, ). Self‐report measures of mate value typically ask participants to self‐assess socially desirable and sexually desirable traits such as physical attractiveness, health, industriousness, intelligence, social status, relationship fidelity, generosity, and financial prospects.…”
Section: Mate Retentionmentioning
confidence: 99%
“…Researchers has found that men with physical traits commonly associated with masculinity, such as greater height, broader shoulders, and smaller hip-to-waist ratios, tended to have more symmetrical bodies. Similarly, women who were more symmetrical tended to have more typical feminine traits, such as larger hips, longer and more slender legs, and larger breasts (Cloud and Perilloux, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…Other studies conducted on homogenous (most frequently college-educated western) populations have found similar results. For example, one centering on British university students also concluded that a WHR of 0.7 was an evolved universal preference (see [23] ; for a more recent example, see [29] ). Universal preferences for other body measurements have been proposed as well.…”
Section: Introductionmentioning
confidence: 99%